The two-dimensional elasticity of a chiral hinge lattice metamaterial. (1st June 2018) - Zhang, Wenjiao; Neville, Robin; Zhang, Dayi; Scarpa, Fabrizio; Wang, Lifeng; Lakes, Roderic
Abstract: We present a lattice structure defined by patterns of slits that follow a rotational symmetry (chiral) configuration. The chiral pattern of the slits creates a series of hinges that produce deformation mechanisms for the lattice due to bending of the ribs, leading to a marginal negative Poisson's ratio. The engineering constants are modeled using theoretical and numerical Finite Element simulations. The results are benchmarked with experimental data obtained from uniaxial and off-axis tensile tests, with an overall excellent agreement. The chiral hinge lattice is almost one order of magnitude more compliant than other configurations with patterned slits and – in contrast to other chiral micropolar media – exhibits an in-plane shear modulus that closely obeys the relation between Young's modulus and Poisson's ratio in homogeneous isotropic linear elastic materials.